Dobera glabra (Forssk.) Poir. (Salvadoraceae); phenolic constituents of the aqueous leaves extract and evaluation of its anti-inflammatory, analgesic activities. Issue 2 (February 2021) - Emam, Mahmoud; Moustafa, Passant E.; Elkhateeb, Ahmed; Hussein, Sameh R.; Marzouk, Mona M.; Abd El-Rahman, Sahar S.; Abdel-Hameed, El-Sayed S.; Abdel-Rahman, Rehab F.
Abstract: Background: The plant kingdom is considered one of the most common sources for structural and biological diversity. In particular, the wild category acquires our attention to investigate the phytochemical and the biological evaluations. Methods: Dobera glabra was exposed to phytochemical examination using HPLC-ESI-MS analysis. Furthermore, the anti-inflammatory activity was evaluated using carrageenan-induced rat paw edema model, whereas both the central and peripheral analgesic activities were tested via hot plate test in rats and acetic acid-induced writhing in mice, respectively. Results: Twenty phenolic compounds of D. glabra aqueous leaves extract were emphasized by liquid chromatography coupled with mass spectrometry. Moreover, D. glabra exhibited both anti-inflammatory and peripheral analgesic activities. Furthermore, D. glabra significantly decreased the immune expression of MMP-9, TNF-α and TGF-β1 in the hind paw of rats. Conclusion: D. glabra possess peripheral anti-nociceptive and anti-inflammatory effects in rats mediated through its anti-oxidant and anti-inflammatory activities. The activity of D. glabra leaves extract might be attributed to the presence of hydroxy and keto structures. Abstract : Dobera glabra ; Anti-Inflammatory; Analgesic; Flavonoids; Rat